2018
DOI: 10.5513/jcea01/19.2.2150
|View full text |Cite
|
Sign up to set email alerts
|

The influence of addition of Lactobacillus plantarum and Lactobacillus brevis on the fermentation quality of silages from permanent grassland

Abstract: The aim of the experiment was to determine the influence of the addition of Lactobacillus plantarum and Lactobacillus brevis on the quality of the fermentation process of silage from the permanent grassland after 12 months of storage in silage bags. In the phytomas of the permanent grassland the proportion of grass was 86% (with the prevalence of Arrhenatherum elatius), herbs 13% and leguminous 1%. The experiment consisted of two variants: variant C (control-without additive) and variant A with the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These results were also achieved by Alba-Mejía et al (2016), where biological additive addition ( ho LAB + he LAB) caused a statistically significant (P <0.05) higher acidity of water extract from 1,366.00 mg KOH to 1,636.7 mg KOH in grass silage. On the other hand, Juráček et al (2018) showed a statistically significant (P <0.05) lower acidity of water extract using homofermentative and heterofermentative strains of LAB in grass silages. The decrease in pH in current experiment was also statistically significant, and these results were also confirmed by Choi et al (2015Choi et al ( , 2016Choi et al ( , 2017.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These results were also achieved by Alba-Mejía et al (2016), where biological additive addition ( ho LAB + he LAB) caused a statistically significant (P <0.05) higher acidity of water extract from 1,366.00 mg KOH to 1,636.7 mg KOH in grass silage. On the other hand, Juráček et al (2018) showed a statistically significant (P <0.05) lower acidity of water extract using homofermentative and heterofermentative strains of LAB in grass silages. The decrease in pH in current experiment was also statistically significant, and these results were also confirmed by Choi et al (2015Choi et al ( , 2016Choi et al ( , 2017.…”
Section: Resultsmentioning
confidence: 90%
“…Long-term stability and fermentation quality can be achieved mainly by adding biological silage additives during silage preparation (Arasu et al, 2014). These silage additives are usually divided into two groups as homofermentative ( ho LAB) and heterofermentative ( he LAB) strains of lactic acid bacteria (Juráček et al, 2018). Therefore, the genera Lactobacillus, Lactococcus, Pediococcus, Leuconostoc, Enterococcus, and Weissella are most commonly associated with silage (Arasu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%